FLAVONOLS FROM THE LEAVES Lygodium microphyllum (Lygodiaceae) - Kuncoro, Hadi; Farabi, Kindi; Julaeha, Euis; Rijai, Laode; Shiono, Yoshihito; Supratman, Unang (Jurnal Kimia (Journal of Chemistry); Vol. 11. No. 1 Januari 2017, 2017)
Flavonol compounds, quercetin ( 1 ) and quercetin-3- O -?-D-glucopyranoside ( 2 ) have been isolated from the ethyl acetate extract of Lygodium microphyllum leaves. The chemical structures of flavonol compounds were identified based on spectroscopic data and by comparison of spectral data obtained previously. The discovery of flavonol compounds in Lygodium microphyllum was shown in this study for the first time.
Keywords: Lygodium microphyllum, quercetin, quercetin-3-O-?-D-glucopyranoside, Lygodiaceae.